Cognitive Development of Adult Undergraduate Students: Cohort and Non-Cohort Settings - Royce Ann Collins (Educational Considerations, 2006)
In response to the increased number of adults in the student population, colleges and universities began offering courses in a variety of formats to accommodate the working adult’s schedule. These formats include, but are not limited to, intensive weekend courses and accelerated cohort programs.